2020
DOI: 10.1111/jsr.12984
|View full text |Cite
|
Sign up to set email alerts
|

Blue‐blocking glasses as additive treatment for mania: Effects on actigraphy‐derived sleep parameters

Abstract: Improvement of sleep is a central treatment goal for patients in a manic state. Blue‐blocking (BB) glasses as adjunctive treatment hasten overall recovery from mania. This method is an evolvement from dark therapy and builds on the discovery of the blue‐light‐sensitive retinal ganglion cell that signals daytime to the brain. We report effects of adjunctive BB glasses on actigraphy‐derived sleep parameters for manic inpatients as compared to placebo. Hospitalized patients with bipolar disorder in a manic state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…Moreover, because light plays a key role in BD, effective chronotherapeutic intervention for BD is strongly indicated (Gottlieb et al, 2019). Previous studies have reported that the use of blue-blocking glasses before bedtime improved sleep quality in patients with BD (Henriksen et al, 2020; Phelps, 2008). Our results support this evidence.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, because light plays a key role in BD, effective chronotherapeutic intervention for BD is strongly indicated (Gottlieb et al, 2019). Previous studies have reported that the use of blue-blocking glasses before bedtime improved sleep quality in patients with BD (Henriksen et al, 2020; Phelps, 2008). Our results support this evidence.…”
Section: Discussionmentioning
confidence: 91%
“…Another experimental study in 19 healthy adults reported that exposure to a short wavelength (460 nm) significantly prolonged SOL, decreased SE, increased WASO and shortened TST compared with exposure to a long wavelength (620 nm) (Green et al, 2017). Furthermore, a randomized controlled trial in patients with acute mania recently reported that blue-blocking glasses, which virtually eliminated blue wavelengths, when compared with placebo glasses, significantly improved actigraphy sleep parameters, including SE and WASO (Henriksen et al, 2020). Although our results showed that the irradiance of the blue wavelength range was significantly associated with a longer WASO, we obtained similar results for the irradiance of green and red wavelength ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Barbini et al (2005) found 14 hours of dark (6 p.m. to 8 a.m., n = 16) adjunctive to treatment as usual (TAU) produced rapid antimanic response compared with TAU alone ( n = 16) over 3 days. Henriksen et al (2020) found amber (blue-blocking) glasses (6 p.m. to 8 a.m., n = 12) were superior to clear glasses (6 p.m. to 8 a.m., n = 11) in reducing manic symptoms across 7 days of intervention (effect size = 1.86). Barbini et al (2005) note no adverse events, while 2 of 12 patients in the treatment group developed depressive symptoms (successfully addressed by delaying or stopping use of the amber glasses).…”
Section: Treatmentsmentioning
confidence: 95%
“…Notably, the early studies showed a keen interest in treatment response (or change in illness with treatment withdrawal), but these themes were not pursued to a definitive conclusion. However, this theme is now drawing interest again and two recent studies used actigraphy to explore RAR and acute treatment outcome, namely ketamine infusions for depression (albeit in sample with many more UP than BD cases) and inpatient treatment of mania (such as Blue Blocking Glasses) (Duncan et al 2017 ; Henriksen et al 2020 ). The map also highlights evidence that clinical depressive symptoms are associated with robustness of circadian rhythm (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent response (day 1 & 3 post-infusion) was characterized by higher amplitude & increased mesor Krane-Gartiser, Norway ( 2018 ) 3 Series of BD-I cases with > = 2 admissions (over 1–6 months) ~ 50 b 1d per admission Intra-individual 24-h activity patterns for recurrences of the same polarity show similar patterns; but episodes with different polarity show intra-individual differences in activity patterns. Acute phases were characterized by greater variation between rest-activity and periods with distinct irregularity in activity (measured by sample entropy) in all cases Averill, New Zealand ( 2018 ) 2 N = 24; 22 Unipolar Depression; 2 BD Depression 38 ± 14; 37% 17d Inpatients were recruited to a study of activity, psychomotor speed & treatment response; usable actigraphy data available from 16 individuals (2 receiving lithium) Change in 24-h activity count was correlated with treatment response Data from consumer grade activity monitor did not correlate with outcomes Kaplan, USA ( 2018 ) 40 Inter-episode BD I (with insomnia) 39 ± 14; 70% 14d (7d pre- & 7d post-intervention) 58 patients were randomized to a two-arm trial; 40 participated in a one session intervention experiment actigraphy data were available on 29 A behavioural intervention (Rise-Up: aimed at overcoming sleep inertia) was compared with a control condition (education: PE) Individuals in the Rise-Up group were significantly more active in the 1 st hour upon waking compared to PE Henriksen, Norway ( 2020 ) 20 BD-I, Mania 45 ± 13; 70% 2d (baseline & day 5) The trail recruited 32 individuals: this study reports data for 20; 10 inpatients were allocated to the blue blocking glasses (BBG) & 10 to placebo glasses 60% of all cases were receiving lithium At day 5: SE improved more in the BBG compared with the control group (4% v 0%). The BBG group showed lower activity count during the sleep period (L5) & lower WASO & a trend for lower FI Knapen, Netherlands ( ...…”
Section: Appendixmentioning
confidence: 99%